Media Pembelajaran Interaktif berbasis Realitas Tertambah (Studi Kasus Mata Pelajaran Fisika Besaran dan Satuan) - Achmad Zulfajri Syaharuddin; Fizar Syafaat; Furqan Zakiyabarsi (Prodi Sistem Informasi UIN Alauddin, 2022)
To this century, education still hold crutial role to further human culture, especially in Indonesia. However, not everyone have the same motivation to learn, although has guided by professional educator. This can be proven from the collected data by Program for Internation Student Assessment (PISA) that Indonesia place in 74 from 79 country with the lowest literacy rate and based on research from United Nation Educational, Scientific and Cultural Organization (UNESCO), only 1 in a 1000 Indonesian has high literacy rate. Beside of it, the interest of calculus also decrease and it’s collerated to research about adversity of learn Physics. To overpass the gap, an interactive learning media needed to help student understand the course. Augmented Reality comes as offered solutio which proven by conducted trials of learning media made to 37 anonym respondent. The result obtained is 81,65% respondent Strongly Agree to learning media created.